PEMAFAATAN SUMBER INFORMASI JURNAL DAN BUKU ELEKTRONIK DI PERPUSTAKAAN UNIVERSITAS PADJADJARAN - -, Rohanda; Winoto, Yunus (Edulib, 2017)
Electronic journals have easy advantages in terms of access, compared withprinted journals and other electronic books. An electronic journal appears first compared to a printed journal. Based on data in 2015 access to electronic journals is higher compared to printed journals and access to electronic books has increased from before. The purpose of this study to determine the paradigm, functionality and reasons students use electronic journalsand electronic books. The approach used is qualitative with case study method expalanatoris. The findings obtained that there is a paradigm shift from manual to electronic. Students are more comfortable using electronic journals and electronic books. This implies the condition of UPT Unpad library that experienced a decrease in student visits.